Depressive symptoms, emotional support and activities of daily living disability onset: 15-year follow-up of the Bambuí (Brazil) Cohort Study of Aging - Juliana Lustosa Torres; Erico Castro-Costa; Juliana Vaz de Melo Mambrini; Sérgio William Viana Peixoto; Breno Satler de Oliveira Diniz; Cesar de Oliveira; Maria Fernanda Lima-Costa (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2018)
Psychosocial factors appear to be associated with increased risk of disability in later life. However, there is a lack of evidence based on long-term longitudinal data from Western low-middle income countries. We investigated whether psychosocial factors at baseline predict new-onset disability in long term in a population-based cohort of older Brazilians adults. We used 15-year follow-up data from 1,014 participants aged 60 years and older of the Bambuí (Brazil) Cohort Study of Aging. Limitations on activities of daily living (ADL) were measured annually, comprising 9,252 measures. Psychosocial factors included depressive symptoms, social support and social network. Potential covariates included sociodemographic characteristics, lifestyle, cognitive function and a physical health score based on 10 self-reported and objectively measured medical conditions. Statistical analysis was based on competitive-risk framework, having death as the competing risk event. Baseline depressive symptoms and emotional support from the closest person were both associated with future ADL disability, independently of potential covariates wide range. The findings showed a clear graded association, in that the risk gradually increased from low emotional support alone (sub-hazard ratio - SHR = 1.11; 95%CI: 1.01; 1.45) to depressive symptoms alone (SHR = 1.52; 95%CI: 1.13; 2.01) and then to both factors combined (SHR = 1.61; 95%CI: 1.18; 2.18). Marital status and social network size were not associated with incident disability. In a population of older Brazilian adults, lower emotional support and depressive symptoms have independent predictive value for subsequent disability in very long term.